Intrusion detection and prevention using Bayesian decision with fuzzy logic system - Sekar, Satheeshkumar; Parvathy, Palaniraj Rajidurai; Gupta, Gopal Kumar; Rajagopalan, Thiruvenkadachari; Basavaraddi, Chethan Chandra Subhash Chandra Basappa; Padmanaban, Kuppan; Murugan, Subbiah (International Journal of Electrical and Computer Engineering (IJECE), 2025)
Nowadays, intrusion detection and prevention method has comprehended the notice to decrease the effect of intruders. denial of service (DoS) is an attack that formulates malicious traffic is distributed into an exacting network device. These attackers absorb with a valid network device, the valid device will be compromised to insert malicious traffic. To solve these problems, the Bayesian decision model with a fuzzy logic system based on intrusion detection and prevention (BDFL) is introduced. This mechanism separates the DoS packets based on the type of validation, such as packet and flow validation. The BDFL mechanism uses a fuzzy logic system (FLS) for validating the data packets. Also, the key features of the algorithm are excerpted from data packets and categorized into normal, doubtful, and malicious. Furthermore, the Bayesian decision (BD) decide two queues as malicious and normal. The BDFL mechanism is experimental in a network simulator environment, and the operations are measures regarding DoS attacker detection ratio, delay, traffic load, and throughput.